STRATEGIC LEADERSHIP AND NATIONAL SECURITY IN A TIME OF GLOBAL GEOPOLITICAL CRISIS: MAQASID AL-SHARI'AH'S PERSPECTIVE ON INDONESIA UNDER PRESIDENT PRABOWO SUBIANTO - Rahman Fanani; Moch. Nurcholis; Mowafg Masuwd (MIYAH: Jurnal Studi Islam, 2026)
The inauguration of Prabowo Subianto as the President of Indonesia marks a significant shift in the nation’s foreign and defense policy toward "Strategic Assertiveness." In an era defined as the "Age of Chaos," characterized by the erosion of multilateralism and intense US-China competition, Indonesia faces multifaceted threats ranging from maritime sovereignty to food and energy security. This report examines Prabowo’s leadership style through the lens of Maqashid al-Syariah, focusing on how his policies aim to protect the five essential elements of human well-being (al-maqasid al-khamsah). By employing a qualitative-descriptive methodology, the analysis reveals that Prabowo’s "firm, charismatic, and task-oriented" leadership embodies the Quranic principle of "I’dadul Quwwah" (preparation of strength) as mandated in Surah Al-Anfal 60. His focus on defense modernization and food self-sufficiency aligns with the preservation of life (Hifz an-Nafs) and wealth (Hifz al-Mal). However, the implementation of "polite democracy" and a military-dominant cabinet sparks debate regarding the balance between national stability and civil liberties. This research concludes that while Prabowo’s assertive stance is necessary for national survival in a multipolar world, it must be balanced with transparency and democratic accountability to ensure genuine public interest (maslahah).